Introducing arduino as an effective online distance learning tool in final year project for chemical engineering student - Zainal Alama, Muhd Nazrul Hisham; Samsudin, Sani Amril; Kamaruddin, Mohd Johari; Zakaria, Zaki Yamani; Othman, Raudhah (2022)
The Covid-19 pandemic crisis has transformed project-based education into virtual lab and non-experimental work. Student final year project (FYP) course particularly is in critical since it has bigger credit, involves more skill set development and conducted in two semesters. In this work, we highlighted the implementation of Arduino in FYP where the main objective of the work is to investigate the effectiveness of Arduino home based final year project for chemical engineering student’s cognitive, psychomotor and affective skills. Comparison on learning satisfaction, obtainment of student skills and reflection from both student and examiners were thoroughly discussed. Surveys showed that student were reluctant to carry out the project in the beginning; however, they began to show more interest on the project as they started to understand the basic principle of Arduino operation. Both students and the examiners agreed that Arduino-based project had given significant impact on student cognitive skills at the level of Application, Analysis, Synthesis and Evaluation. On top of that, the psychomotor and affective skills were simultaneously and successfully developed in the remote learning process. It is evident that the proposed Arduino home-based FYP is affordable and effective for the development of student skill sets despite being supervised virtually.